Preliminary Study of the Spring-back/Spring-go Phenomenon in the V-Bending Process Using SGCC Steel Thin Material - Muhammad Rian Kurniadi; Jatira Jatira; Khoirudin; Rizki Aulia Nanda; Rama Kurniawan; Otong Jaelani; Dibyo Setiawan (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
This research analyses v-bending results using galvanized SGCC (JIS G 3302) sheet steel. The accuracy of the angle and dimensions of the bending results are the significant elements of the bending process that must be achieved. The bending spring-back/spring-go phenomenon has an impact on bending angle accuracy. If proper parameters are chosen, the spring-tub/spring-go angle should be minimized. This study aimed to see how the proposed v-bending process affected the spring-tub/spring-go angle value. An experimental approach was selected in this study. V-die bending opening, V-die punch angle, V-die punch speed, and bending force are all input parameters for the v-bending process. Meanwhile, in this study, galvanized steel with a thickness of 1.2 mm was used. The results of the ANOVA evaluation showed that the v-die punch speed and bending force are two parameters that affect the response of the variable, with a percentage contribution of 31.0% each. The minimum spring-back angle was found in the second sample, while the minimum spring-go angle was found in the fourth sample